IMPLEMENTASI PEMBIASAAN TADARUS AL-QUR’AN DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK KELAS VIII MTS AL-AHSAN TANAH SEREAL KOTA BOGOR - Fitri Amalia; Syarifah Gustiawati; Hasan Basri Tanjung (KOLONI, 2022)
This study aims to determine (1) the Implementation of Al-Qur'an Habituation in the Formation of Religious Character of Class VIII Students of MTS Al-Ahsan Bogor. (2) The Impact of the Implementation of Tadarus Al-Qur'an Habituation in the Formation of the Religious Character of Class VIII Students of MTS Al-Ahsan Bogor. This study uses a descriptive qualitative approach. It was carried out from June 1, 2022 to July 20, 2022. The research location was at MTS Al-Ahsan Bogor. In the data collection procedure the author uses observation techniques, interview techniques and documentation techniques. Meanwhile, in data analysis, researchers used data collection, data reduction, data presentation and drawing conclusions. The results of this study found that (1) The implementation of the habituation of tadarus Al-Qur'an was carried out before the teaching and learning process began, namely at 07:00 WIB. every Tuesday to Friday, except on Mondays because there is a flag ceremony. The place for the implementation of the Qur'anic tadarus is carried out in the mosque. This activity is not only attended by students but also by teachers and staff participating in carrying out tadarus Al-Qur'an. (2) The impact of the implementation of tadarus Al-Qur'an habituation in the formation of the religious character of students of class VIII MTS Al-Ahsan Bogor, namely, Obedience to Allah, namely students having morality towards teachers by applying 5S (greetings, smiles, greetings, polite, polite). Patience is being able to control emotions during the learning process. Sincerity is sincerely carrying out the habit of tadarus Al-Qur'an because of Allah SWT. Honest, namely when the exam students work independently by not cheating. Keywords: Habituation, Tadarus Al-Qur'an, Religious Character